Liberal Education Partisan Epistemology (Universitas Muhammadiyah Sidoarjo, 2015)
Liberal education generally believed that true education must be universal and free from indoctrinative practices. It is moving from liberal education principles that uphold the values that are vital to the moral and intellectual development of man, such as critical thinking, personal autonomy and pluralism of thought. However, when juxtaposed with other variants of educational paradigm promoted mainly by radicals and conservatives, it was not easy to be realized. Liberal education proved epistemologically partisan and incompletely sterile from practices of indoctrination.